PLANT BIOACTIVE ; CAROTENOIDS, POLYPHENOLS AND FLAVONOIDS IN IMPROVING THE IMMUNE SYSTEM AGAINST COVID-19 INFECTION - James Ngginak; Sonya T.M. Nge; Tiodor S. J. Manalu; Paulus D.B. Murti; Yanti Daud (Biolearning Journal, 2023)
COVID-19 (coronavirus) is a new type of virus that can cause disease in animals and humans. This type of virus causes a crisis or threat to human life in 2020. Before an ideal vaccine or drug is found to prevent COVID-19 infection, steps or approaches are needed that can break the chain of infection. Several things that can be done to prevent COVID-19 infection are to take advantage of the chemical content of natural ingredients, maintain nutritional intake, maintain the resilience of the body's immune system and adhere to health protocols. The public needs to be made aware of the use of natural metabolites in order to maintain the body's defense system. Carotenoids, polyphenols and flavonoids are a group of secondary metabolites in plants that can physiologically increase the body's immune system against bacterial and viral infections. Red, yellow pigments in plants and some organisms known as coarotenoids have the ability to enhance the body's immune response or cellular immune system. While polyphenols and flavonoids are a unique group of phytochemicals in fruits, vegetables and herbs. This component has the potential to inhibit viral replication. People are expected to use plant chemical compounds to improve the body's immune system.